PENERAPAN MANAJEMEN BISNIS SYARIAH DALAM PRAKTIK JUAL BELI EMAS DI NILAU TAPAN PESISIR SELATAN - Anju Sri Indra; Sofia Ridha (Adisam Publisher, 2026)
The practice of buying and selling gold in Nilau Tapan, Pesisir Selatan Regency, is still carried out traditionally and has not fully implemented the principles of structured business management. Business management is more based on experience, habits, and trust between traders and buyers that have been established for a long time. However, the values of honesty and trust are still upheld by traders in carrying out daily trading activities, such as in determining the weight, content, and price of gold. However, there is no systematic business planning, regular record keeping, and structured supervision have the potential to cause an imbalance of information between traders and buyers. This situation prompts the necessity for a study to evaluate the degree to which gold trading practices in Nilau Tapan adhere to the fundamentals of sharia business management. The purpose of this inquiry is to examine the application of sharia business management within gold transaction activities in Nilau Tapan, South Coastal Regency. The methodology applied is field investigation with a qualitative descriptive perspective. Information was gathered via direct monitoring at the study site, dialogues with gold merchants and customers, along with records associated with gold trading operations at Nilau Tapan Market. The data analysis mechanism is performed through the phases of data gathering, data condensation, data display, and conclusion formulation. The study findings indicate that the execution of business management in gold trading practices in Nilau Tapan remains elementary and conventional. Management functions such as planning, organizing, implementation, and supervision have not been formally and in writing, but are carried out based on the experience and habits of the trader. However, viewed from the perspective of sharia business management, the practice of buying and selling gold in Nilau Tapan has reflected sharia values such as honesty (shiddiq), trust, justice, responsibility, and transparency in determining the weight, content, and price of gold. Thus, even though business management has not been structured in a modern way, the practice of buying and selling gold in Nilau Tapan is basically in accordance with the principles of sharia business management.